Diversity of butterflies (Lepidoptera) across rainforest transformation systems in Jambi, Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Panjaitan R, Drescher J, Buchori D, Peggie D, Harahap IS, Scheu S, Hidayat P. 2020. Diversity of butterflies (Lepidoptera) across rainforest transformation systems in Jambi, Sumatra, Indonesia. Biodiversitas 21: 5119-5127. The high rate of land conversion has put pressure on biodiversity, especially in the tropics. The lowlands of Sumatra, for example, are dominated by increasingly extensive areas of oil palm and rubber monoculture plantations, while rainforests are continuously vanishing. The status of many rainforest animal populations, including iconic insect groups such as butterflies, is largely unclear. With a rapid assessment approach, we studied butterflies along land-use gradients from lowland rainforest, via jungle rubber plantations (rubber agroforest system), to monocultures of rubber and oil palm in Jambi Province, Sumatra. Butterflies were caught in a nested replication design at eight research plots at each of the forest, jungle rubber, and rubber and oil palm locations. Butterfly abundance was the highest in the rainforest (204.3±82.1), slightly lower in the jungle rubber and oil palm areas (164.9±61 and 169.3±94.9, respectively), and the lowest in the rubber plantation (108.8±38.5). Similarly, butterfly species richness was the highest in the forest and jungle rubber areas (47.1±7.7 and 38.8±7.6, respectively), followed by the oil palm area (33.3±9.8), and the lowest in the rubber plantation (26.1±9.1). Likewise, Shannon-Wiener diversity was the highest in the rainforest, at an intermediate level in the jungle rubber, and lowest in the oil palm and rubber plantations. Butterfly community composition in the rainforest was very different from that in the other three land-use systems, in which it was similar. Overall, the study demonstrates that rainforest butterfly communities cannot be sustained in agricultural systems, highlighting the importance of rainforests for conserving the diversity of arthropods.
Keywords: Sumatra, butterflies, riparian sites, rainforest transformation, EFForTS project